Scanning transmission electron microscopy investigations of self-forming diffusion barrier formation in Cu(Mn) alloys on SiO2 - Lozano, J; Bogan, J; Casey, P; McCoy, A; Hughes, G; Nellist, P (American Institute of Physics Inc., 2013)
Scanning transmission electron microscopy in high angle annular dark field mode has been used to undertake a characterisation study with sub-nanometric spatial resolution of the barrier formation process for a Cu(Mn) alloy (90%/10%) deposited on SiO2. Electron energy loss spectroscopy (EELS) measurements provide clear evidence for the expulsion of the alloying element to the dielectric interface as a function of thermal annealing where it chemically reacts with the SiO2. Analysis of the Mn L23 intensity ratio in the EELS spectra indicates that the chemical composition in the barrier region which has a measured thickness of 2.6 nm is MnSiO3. © 2013 Author(s).